A Simplified Wiener Based Model Predictive Control For Distillation Column - Iqbal, Imam Mujahidin (2012)
The distillation column process requires a large amount of energy, thus efficiently controlling the column can significantly minimize the operational costs. Nonlinear model predictive control (NMPC) is one of the best control strategies available to control such a column. In the NMPC implementation, the linearization technique is often used to guarantee the global optimum solution and to reduce the computational burden. One of the promising control schemes that uses the linearization technique is the Wiener based Linear Control (WLC) scheme which uses the inverse of the nonlinear block, and does not require the derivative of the model.